2020
DOI: 10.1002/jor.24860
|View full text |Cite
|
Sign up to set email alerts
|

Location and magnitude of capsular injuries varies following multiple anterior dislocations of the shoulder: Implications for surgical repair

Abstract: Capsular injuries can occur during multiple shoulder dislocations. The purpose of this study is to evaluate the location and magnitude of glenohumeral capsular injury following multiple dislocations. We hypothesized that the magnitude of capsular injury would increase and the location of peak injury would vary depending on the number of dislocations. Seven fresh‐frozen cadaveric shoulders were used. A 7 × 11 grid of strain markers was affixed to the anteroinferior capsule. Each joint was then mounted to a six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…As the force required for dislocation decreases, 28 the humeral head goes further over the rim of the glenoid or the capsule could be experiencing micro‐tears. The previous study demonstrated location and magnitude of non‐recoverable strain varied following multiple dislocations 17 . On the other hand, the mean direction of the non‐recoverable remained consistent through multiple dislocations in this study.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…As the force required for dislocation decreases, 28 the humeral head goes further over the rim of the glenoid or the capsule could be experiencing micro‐tears. The previous study demonstrated location and magnitude of non‐recoverable strain varied following multiple dislocations 17 . On the other hand, the mean direction of the non‐recoverable remained consistent through multiple dislocations in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, no capsular injuries were observed in these regions. Magnitude and location of non‐recoverable strain were analyzed in a similar manner as previously described 17 . Finally, the categorization of the mean direction of non‐recoverable strain is binary, parallel, or perpendicular.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations